Retention of Alzheimer Disease Research Participants. (October 2019) - Grill, Joshua D.; Kwon, Jimmy; Teylan, Merilee A.; Pierce, Aimee; Vidoni, Eric D.; Burns, Jeffrey M.; Lindauer, Allison; Quinn, Joseph; Kaye, Jeff; Gillen, Daniel L.; Nan, Bin
Abstract : Introduction: Participant retention is important to maintaining statistical power, minimizing bias, and preventing scientific error in Alzheimer disease and related dementias research. Methods: We surveyed representative investigators from NIH-funded Alzheimer's Disease Research Centers (ADRC), querying their use of retention tactics across 12 strategies. We compared survey results to data from the National Alzheimer's Coordinating Center for each center. We used a generalized estimating equation with independent working covariance model and empirical standard errors to assess relationships between survey results and rates of retention, controlling for participant characteristics. Results: Twenty-five (83%) responding ADRCs employed an average 42 (SD=7) retention tactics. In a multivariable model that accounted for participant characteristics, the number of retention tactics used by a center was associated with participant retention (odds ratio=1.68, 95% confidence interval: 1.42, 1.98; P <0.001 for the middle compared with the lowest tertile survey scores; odds ratio=1.59, 95% confidence interval: 1.30, 1.94; P <0.001 for the highest compared with the lowest tertile survey scores) at the first follow-up visit. Participant characteristics such as normal cognition diagnosis, older age, higher education, and Caucasian race were also associated with higher retention. Conclusions: Retention in clinical research is more likely to be achieved by employing a variety of tactics. Abstract : Supplemental Digital Content is available in the text.